Learning of Writing in a Non-Mother Tongue: the Case of Tarahumara Children - Efrén Viramontes-Anaya; Lylia Ana Morales-Sifuentes; Luis Manuel Burrola-Márquez (Revista Electrónica Educare)
Abstract. This study analyzes the development of writing in Spanish among bilingual Tarahumara children (Chihuahua, Northern Mexico), from different perspectives: 1) A psychogenetic perspective, focusing on how the writing process is constructed by Tarahumara children; 2) A social perspective, focusing on the children’s family context, as well as the cultural and economic characteristics of their community, and; 3) A pedagogical perspective, focusing on the learning environments of two different kinds of schools these children attend (a “regular” school and a bilingual school for indigenous children). This study tries to identify how different factors have an impact on the development of writing. Data was collected for this multiple-case study through on-site observation, interviews and videotaping class sessions at both schools. Children’s notebooks and writing products were also collected. The data was analyzed transversally considering events, people and contexts related to the writing process. The results were interpretations on the social, cultural, cognitive and pedagogical factors that were perceived, associated to the learning process of how to write in a non-mother tongue, in the case of migrant indigenous children, in an environment different from that of their ancestors. The study was based on the hypothesis that, in the circumstances of the studied cases, it is better for these children to learn first how to write in their second language and, then, in their mother tongue, if necessary.